Optimization of xanthophylls extraction from Marigold extractum with supercritical CO2 by response surface methodology - Quancheng, Zhou; Guihua, Sheng; Jingrong, Huang; Ting, Zhou; Quanhong, Li (International Journal of Agricultural and Biological Engineering, 2010)
In this work, xanthophylls were extracted from Marigold using supercritical CO2. A response surface experimental design was used to optimize operating conditions for extraction pressure (22-30 MPa), extraction temperature (50-60